Perfil sociodemográfico e tabágico dos pacientes do programa de tratamento de tabagismo do serviço de pneumologia do Hospital Universitário de Santa Maria - Alves, Teodora Pereira (2023)
Introduction: Smoking is one of the most important public health problems, although it is a treatable and preventable condition. Objectives: The objective of this study was to evaluate the sociodemographic and tabagic profile and factors associated with smoking cessation in a treatment program of the pneumology service at University Hospital of Santa Maria (Husm). Material and method: Observational, descriptive, longitudinal, prospective and retrospective study. The sample consisted of 29 of 41 referred patients. Inclusion criteria were being over 18 years of age and being referred by Husm outpatient clinics. Exclusion criteria were being pregnant, non-attendance to the first meeting of the group and the presence of evident cognitive or emotional deficiency, verified in the initial clinical evaluation. During the first meeting, the motivation for smoking cessation was evaluated, and all participants received information about cognitive-behavioral and drug treatment, according to the National Cancer Institute (Inca). When declaring themselves ready to start treatment, the individuals completed the standard clinical evaluation protocol, with sociodemographic data, smoking history, alcohol use, associated comorbidities, degree of motivation and degree of nicotine dependence. Results: There was a predominance of women (58.6%), and the predominant age group was from 35 to 49 years. Most of the participants were married (72.4%), with education up to eight years of study (58.6%); overweight and obese (69%); presented depression and anxiety (72.4%) and used alcohol on weekends (51.7%). The onset of smoking was, on average, at 15 years of age. Participants smoked more than 20 cigarettes a day. Smoking lasted at least 30 years, with a medium to high degree of smoking dependence. Participants had more than three previous attempts to quit smoking. Of the 29 patients, 17 quit smoking (58%). There was a statistically significant association between smoking cessation and the number of meetings or sessions (p = 0.025). There was no statistically significant association between cessation and the other variables of the smoking profile, as well as with the variables of the sociodemographic profile. Conclusion: The present study described the sociodemographic characteristics of the sample and showed that the chance of quitting smoking in this group was significantly associated with the participation of patients in four or more sessions.